#TITLE_ALTERNATIVE# - SETYANINGRUM (NIM 25399013); Pembimbing: Prof.Dr.Ir. Harun Sukarmadijaya, M.Sc., ENDANG
Most of the problem of waste disposal site in Indonesia is among others leachate pollution into the ground water or river. This problem arises due to the unfulfillment of the location with refer to SNI No. 03-3241-1997 and lack of the facilities such as the impermeable bottom layer, the leachate treatment, daily soil cover and the gas venting. Landfill site in Bantar Gebang (108 Ha) belong to DIQ- Jakarta Government is located in City of Bekasi and close to housing area. The people indicate that the pollution into their wells have been done since the landfill site operated in 1989. In accordance with the above mentioned, the researches have been conducted to search the possibility of leachate pollution into the ground water. The research is done in the laboratory and the field, and applied the mathematical model to predict the transport contaminant due to the advection, dispersion and retardation phenomena. Based on the research result, its indicated that the leakage process appeared at the bottom layer of zone I. The leakage is indicated by the value of COD, Chloride and DHL at well SM-Z1 (40 - 60 % of the leachate quality). Analysis has been undergone to 11 wells and 4 soil sample. The following data concludes the result of the research, they are Soil Porosity 0.5 - 0.6, adsorption rate : 24.137 / day, biodegradation rate 0.035-0.045/day, retardation value 26,03 - 31.99, advection at the groundwater flow 0.003011 cm/sec (laboratory scale) and 6.821 x 10 -7 cm/sec (field scale), and dispersion rate DL 0.87015 cm`/sec, DT 0.08715 cm2/sec. Based on the mathematical model simulation (created by Domenico & Schnoor), the deviation of the contaminan concentration in grid area is very high compared to the field measurement.